Prevalence of Low Back Pain in Informal Sectors at a Port Harbor in Pattani Province - Supapvanich, Chompunuch; Musow, Aresow; Pongkasert, Anchalee (Princess of Naradhiwas University Journal, 2019)
This cross sectional descriptive study aimed to determine the prevalence of low back pain and its level in harbor workers who are working in informal sectors. Participants were 217 workerswho completed the interview questionnaire which provided information such as demographic data, history of ill-health, work characteristics, duration of work, low back pain symptoms and management of back pain symptoms. Data were analyzed by using descriptive statistics. Result showed that 149 workers had adverse symptoms of low back pain (68.7%). Pain level was at a score between 6 and 7 (intense to very intense pain) (30.9%). Harbor workers from informal sectors suffered low back pain symptoms during 1 – 3 days (33.6%). For the low back pain treatment, 47% of workers from informal sectors used body massage for healing pain symptoms, followed by 43% who were using poly-medicines. In conclusion, more than half of workers from harbor informal sectors had reported low back pain. Therefore, health care providers and employers should support them by providing knowledge, developing employee’s awareness, supporting tools for moving heavy stuff, and promoting work safety for decreased risks of this occupational disease.